The Role of Transformative Learning in Fostering Identity Development among Learners in Professional Education Programs of Study - Elizabeth P Marlowe; Teresa J Carter (Adult Education Research Conference, 2016)
This roundtable discussion engages participants in exploring how professional identity develops for learners engaged in advanced professional education and how they experience the meaning of what it is to become a professional.
Keywords: professional learning; professional identity formation; transformative learning; medical education; critical incidents